H.D.’s Trilogy: The Multiplicity of Being (ENTHYMEMA, 2015)
This essay is an epistemological interrogation and should be read as one possible approach among others to H.D.’s poetic experiment in Trilogy. It argues that the empiricist tradition provides us with a series of concepts that may help us make sense of the poem, or, rather, understand a little better how the poem makes sense. In this respect, H.D.’s numerous polytheistic mythological allusions can be problematized as being at the service of a philosophy of the human subject, not considered as a fixed, alienated entity, but as a constantly evolving multiplicity whose main activity is to construct new relations or syntheses, thereby endlessly constructing itself in the process.